IMPLEMENTATION OF THE MOBILIZING TEACHER PROGRAM IN IMPROVING THE MORALE OF COLLEAGUES AT SENIOR HIGH SCHOOL 3 PRABUMULIH - Rohliyati Rohliyati; Waspodo Waspodo; Tutut Handayani; Ade Akhmad Saputra (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to analyze the Implementation of the Mover Teacher Program in Improving the Morale of Peers at SMAN Negeri 3 Prabumuli. This research is a qualitative research with a descriptive approach. In collecting data, researchers used several collection techniques, namely interviews, observation, and documentation. Based on the results of this study, the Mover Teacher Program aims to equip teachers with learning and pedagogical leadership skills so that they can advance the learning community inside and outside the education unit, and have the potential to become educational leaders who can create comfort and well-being for students in their respective education units. The ability to promote learning is the driving teacher's ability to motivate and actively participate in the subject teacher's environment to reflect, collaborate, share knowledge and learn from each other to achieve common goals, so as to achieve the goals of learning.